2003
DOI: 10.1023/a:1024420104400
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The terahertz frequency absorption spectraof DNA molecules reflect low-frequencyinternal helical vibrations involvingrigidly bound subgroups that are connectedby the weakest bonds, including thehydrogen bonds of the DNA base pairs,and/or non-bonded interactions. Althoughnumerous difficulties make the directidentification of terahertz phonon modes inbiological materials very challenging, ourresearch has shown that such measurementsare both possible and fruitful. Spectra ofdifferent DNA samples reveal a large nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(69 citation statements)
references
References 26 publications
2
64
0
3
Order By: Relevance
“…Further the observed aneuploidy appeared to be chromosomespecific in agreement with other studies on cellular response induced by chemical or physical stimuli [45]. The authors suggested, as possible mechanism underlying these effects, that THz radiation is able to excite low-frequency collective vibrational modes of biomolecules [45]. Recently the coherent collective vibration models of molecule (e.g., DNA and proton) have been theoretical analysed, indicating that the interaction between these biological systems and THz radiation can produce resonance excitation effect capable to explain mutagenesis effects [46].…”
Section: Thz Radiation Effects On Biological Systemssupporting
confidence: 91%
See 1 more Smart Citation
“…Further the observed aneuploidy appeared to be chromosomespecific in agreement with other studies on cellular response induced by chemical or physical stimuli [45]. The authors suggested, as possible mechanism underlying these effects, that THz radiation is able to excite low-frequency collective vibrational modes of biomolecules [45]. Recently the coherent collective vibration models of molecule (e.g., DNA and proton) have been theoretical analysed, indicating that the interaction between these biological systems and THz radiation can produce resonance excitation effect capable to explain mutagenesis effects [46].…”
Section: Thz Radiation Effects On Biological Systemssupporting
confidence: 91%
“…2 h) than above done. Further the observed aneuploidy appeared to be chromosomespecific in agreement with other studies on cellular response induced by chemical or physical stimuli [45]. The authors suggested, as possible mechanism underlying these effects, that THz radiation is able to excite low-frequency collective vibrational modes of biomolecules [45].…”
Section: Thz Radiation Effects On Biological Systemssupporting
confidence: 89%
“…Far-infrared absorption spectroscopy in the terahertz frequency range provides another access to the low-frequency vibrational excitations of DNA. Besides Fourier-transform spectroscopy [9][10][11] and absorption spectroscopy using tunable terahertz light sources, 12,13 time-domain terahertz spectroscopy became available recently to study optical properties of biomolecules and DNA. [14][15][16][17] In this letter, we use a recently developed terahertz spectrometer based on high-speed asynchronous optical sampling ͑ASOPS͒ to measure the terahertz transmission characteristics of highly oriented wet-spun DNA films.…”
Section: -4mentioning
confidence: 99%
“…Millimeter and submillimeter wave region of electromagnetic (EM) spectrum is traditionally utilized in the astrophysics, remote sensing, defense and security, as well as in biomedical imaging applications [1][2][3][4]. Recently, there is an increased interest in utilization of these frequencies in a range of commercial applications, including broadband communications, motivated mainly by the availability of large bandwidths required for the multigigabit short-range wireless communications [5].…”
Section: Introductionmentioning
confidence: 99%